Revolusi Pembelajaran dan Tantangan Pendidik pada Kurikulum Berbasis Digital - Putri, Evana Eka; Faizin, Moh.; Ma’rifah, Akyuninah (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2022)
Basically, educational curriculum is dynamic. This means that the curriculum will continue to change according to the times. These changes that occur also require a new orientation to education that education must lead to creativity, communicativeness, and cooperation. Currently, education is facing a digitalization era. Where, educators are required to be able to keep up with the times and also be able to carry out their role as carriers of good change in a dynamic environtment. Professional theachers in the digital ra are teachers who in carrying out their professional duties are based on digital era must be able to bring students to adapt to digital and foster students to have high morals with good values in reigious, national and state life. This research was conducted with an approach, where the data were obtained through field research using interviews and library research. The conclusion of this research is that there is a revolution and innovation in learning and curriculum that has a big impact on the woorld of education. Knowledge workers to successfully win and convey digital technology knowledge and produce students who have advanced abilities and skills in knowledge and are able to master digital technology.